Design of a Compact, Reconfigurable, Prosthetic Wrist - Arthur Zinck; Øyvind Stavdahl; Edmund Biden; Peter J. Kyberd (Applied Bionics and Biomechanics)
The design of a prosthetic wrist is the result of compromises between the function and the practicality of the device. Conventional prosthetic wrists use a single degree of freedom to produce pro/supination of the hand. It has not been demonstrated that this is the most functional alignment for a single axis. Previous work by the authors suggests that if the wrist must have only one rotatory axis then a more oblique orientation would be more functional. To test this idea, a compact wrist with a single axis and spherical design has been made that will allow any axis of rotation to be selected and the functional performance of the resulting arm be tested.